Development of Pop-Up Books as COVID-19 Health Promotion Media among 4th Grade of Elementary School Students - Annisa Rizkiyah; I Made Sudana; Yuni Wijayanti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: The proportion of people with asymptomatic infection likely varies with age because of the increasing prevalence of co-morbid conditions in older age groups (thus the risk of severe disease increases with increasing age), and because children are less likely than adults to show clinical symptoms. This means that children have a greater chance of not showing symptoms but can transmit COVID-19 to those closest to them, especially their families. This study aimed to develop a pop-up book as a medium for promoting COVID-19 health in grade 4 elementary school children. Indicators of success in the development if the media is said to be effective.Subjects and Method: This research is Research and Development (RnD) which was carried out in 6 elementary schools, Ternate, North Maluku. A total of 97 grade 4 students were selected in this study. The dependent variable is knowledge and attitude. The Independent Variable is the COVID-19 pop-up Book. Data was collected using a questionnaire. The data were analyzed using the t-test, and the improvement test using the N-Gain.Results: After health promotion interventions using a pop-up book for 4th grade elementary school, knowledge (Mean= 17.18; SD= 0.93) was higher than before (Mean= 16.06; SD= 1.76), the results statistically significant (p< 0.001). The attitude after intervention (Mean= 25.27; SD= 2.14) was higher than before (Mean= 20.12; SD= 3.53), the result also statistically significant (p< 0.001).Conclusion: The COVID-19 pop-up book media is effective for use as a media for health promotion.Keywords: development, pop-up books, COVID-19.Correspondence:Annisa Rizkiyah. Master’s Program in Public Health, Universitas Negeri Semarang. Jl. Kelud Utara III No.15, Petompon, Gajahmungkur, Semarang, 50237 Central Java. Email: rizkiyahannisa09@gmail.com. Mobile: +6281336349206.Journal of Health Promotion and Behavior (2023), 08(02): 85-91DOI: https://doi.org/10.26911/thejhpb.2023.08.02.03